Indicadores de qualidade biológica de um latossolo argiloso sob diferentes sistemas de manejo - Moreira, Macarius Cesar Di Lauro (2016)
The soil microbes quickly respond the changes that the management systems cause in the soil, therefore, are sensitive indicators of biological soil quality. In this context, this study aims to assess the impact of seven management systems (MI) Millet (glaucum Pennisetum), (AP) Oat (Avena strigosa), (MP) Black Mucuna (Stizolobium aterrimum), (EF) pea (pea subsp. arvense) + (AP) Oat (Avena strigosa), (PDG) Till plaster cast (PDE) Till scarified and (SPD) Planting Direct Traditionally, the soil quality bio-indicators, (TOC) Total organic carbon (MO) organic Matter soil, (CBMS) ground biomass carbon (RBS) basal soil respiration (qCO2) respiratory coefficient (qMIC), microbial coefficient (Ds) soil density and carbon and its effects on root growth and the yield of soybeans. It was used the completely randomized design, with seven treatments. Soil samples were carried out in three periods; (PP) pre-plant (PF) pre-flowering and (PP) after soybean harvest in the period from July 2014 to March 2015 in four replications for each analysis, and samples collected at Layer (0-10 ) from soil. Statistical analysis was performed using Assistat® 7.6 beta software, version 2012 (Smith, 2012). The analyzes were carried out analysis of variance (ANOVA) and treatment means were compared by TUKEY test at 5% significance; Black Mucuna, the pea forage and tillage system were the most suitable for the improvement of biological soil properties. The cover crops and management system does not affect the root growth and yield of soybean grain